A lithium supplement additive and preparation method thereof
By using lithium supplement additives composed of lithium-rich material core and polymer layer, the problems of poor stability and poor lithium supplementation effects of existing lithium supplement additives are solved, and efficient lithium supplementation and battery performance improvement are achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202110183370.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-02-10
AI Technical Summary
The existing lithium supplement additives have poor stability during use and storage, and are prone to react with water and CO2 in the air, resulting in high residual alkali content on the surface, reducing the lithium supplement effect, and making it difficult to carry out industrial production.
The lithium supplement additive is composed of a lithium-rich material core and a polymer layer. The chemical formula of the lithium-rich material core is aNixMyOz·bLi2O. Doping elements M such as Cu, Co, Al, etc. are used to alleviate the reaction between lithium and nickel and air. The polymer layer is coated with the lithium-rich material core to improve stability.
It improves the first charging and discharging efficiency of lithium-ion batteries, increases the battery energy density, reduces the residual alkali of lithium-enhancing additives, enhances its stability, and makes it suitable for industrial production and use.
Smart Images

Figure CN114725539B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion batteries, and in particular to a lithium supplement additive and a preparation method thereof. Background Art
[0002] During the first charging process of the battery, a surface solid electrolyte film (SEI film) will form on the surface of the positive and negative electrodes. The formation of the SEI film will consume the lithium in the battery and convert the lithium into inactive lithium-containing compounds, thereby causing reversible lithium loss, reducing the first efficiency and reducing the battery discharge capacity.
[0003] In order to make up for the lithium loss caused by the formation of the SEI film during the first charge, the existing method is to add lithium supplement additives to the positive electrode or the negative electrode. However, due to the high activity of the existing lithium supplement additives, they are easy to react with water and CO2 in the air, resulting in a high residual alkali content on the surface of the lithium supplement additive, which reduces the lithium supplement effect and causes battery capacity loss. In order to ensure effective lithium supplementation, the existing lithium supplement additives have extremely stringent environmental requirements during use and storage; and in the preparation process, the lithium supplement additives are easily oxidized, difficult to synthesize in large quantities, and not conducive to industrial production. Therefore, it is necessary to provide a lithium supplement additive and a preparation method thereof to solve the problems of poor stability, poor lithium supplement effect and difficulty in industrial production of existing lithium supplement additives. Summary of the invention
[0004] In view of this, the present application provides a lithium supplement additive, which can not only effectively supplement lithium to lithium secondary batteries and improve the initial efficiency of the batteries, but also has good stability and is not easy to react in the air, which is conducive to the production, storage and transportation of the lithium supplement additive. The present application also provides a preparation method of the lithium supplement additive.
[0005] The first aspect of the present application provides a lithium supplement additive, comprising a lithium-rich material core and a shell layer arranged on the lithium-rich material core, wherein the lithium-rich material core comprises an average chemical formula of aNi x M y O z bLi2O lithium-rich material, wherein 0.95≤x≤1, 0.01≤y≤0.05, 1≤z≤1.15, 0.8≤a≤1.1, 0.8≤b≤1.1; M comprises one or more of Cu, Co, Al, Ti, V, Zr and Fe; and the shell layer comprises a polymer layer.
[0006] The lithium supplement additive in this application is aNi x M y O zbLi2O as the lithium-rich material core effectively compensates for the capacity loss of the first charge and discharge of lithium secondary batteries and improves the first charge and discharge efficiency; the doping element M can alleviate the reaction of lithium and nickel with air, thereby inhibiting the generation of residual alkali by the lithium supplement additive, and making the lithium supplement additive have good stability; the polymer layer can effectively isolate the air, thereby further improving the stability of the lithium supplement additive, so that the lithium supplement additive can exist stably in the air, which is beneficial to the production, storage and use of the lithium supplement additive.
[0007] Optionally, the lithium-rich material core includes an inner layer and a doped interface layer, and the doped interface layer is arranged on at least a portion of the surface of the inner layer; and the M is located in the doped interface layer.
[0008] Optionally, the thickness of the doped interface layer is 1 nm-100 nm.
[0009] Optionally, the median particle size D50 of the lithium-rich material core is 2 μm-10 μm, D10 / D50≥0.3, and D90 / D50≤2.
[0010] Optionally, the lithium-rich material core accounts for 90%-99% of the lithium supplement additive by mass.
[0011] Optionally, the polymer layer comprises a polymer, wherein the polymer comprises [C6H7O6Na] n Organic polymers with the structure [C6H7O2(OH)2OCH2COONa] n Organic polymers with [C3H4O2] n Organic polymers with the structure [C3H3O2M a ] n Organic polymers with [C3H3N] n An organic polymer with the structure -[CH2-CF2] n -structure, an organic polymer containing -[NHCO]-structure, an organic polymer containing an imide ring -[CO-N-CO]-structure on the main chain, and one or more of polyvinyl pyrrolidone, wherein M a It is an alkali metal element.
[0012] Optionally, the molecular weight of the polymer is greater than or equal to 100,000.
[0013] Optionally, the polymer includes one or more of polyvinylidene fluoride, sodium alginate, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylic acid salt, polyacrylonitrile, polyamide, polyimide and polyvinyl pyrrolidone. Further, the polymer includes one or more of sodium carboxymethyl cellulose and polyacrylic acid.
[0014] Optionally, the polymer layer further includes a conductive agent, and the conductive agent includes one or more of carbon black, graphite, conductive carbon microspheres, carbon nanofibers, carbon nanotubes, C60 and graphene.
[0015] Optionally, the mass ratio of the polymer to the conductive agent in the polymer layer is 1:(0.3-1.5).
[0016] Optionally, the mass of the polymer layer accounts for 1%-10% of the total mass of the lithium supplementing additive.
[0017] Optionally, the thickness of the polymer layer is 2nm-50nm, and further, the thickness of the polymer layer is 5nm-40nm.
[0018] Optionally, the shell layer further comprises an electrochemically active layer disposed on the surface of the polymer layer, and the electrochemically active layer comprises an electrochemically active material.
[0019] Optionally, the particle size of the electrochemically active material is 30nm-200nm.
[0020] Optionally, the electrochemically active material includes one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium fluorovanadium phosphate, lithium titanate and lithium nickel cobalt manganese oxide.
[0021] Optionally, the electrochemically active material further comprises carbon, and the mass percentage of the carbon in the electrochemically active material is 0.5%-3%.
[0022] Optionally, the electrochemically active layer has a thickness of 100 nm-500 nm.
[0023] Optionally, the electrochemically active layer accounts for 1%-9% of the total mass of the lithium supplement additive; the core accounts for 90%-98% of the total mass of the lithium supplement additive; and the polymer layer accounts for 1%-9% of the total mass of the lithium supplement additive.
[0024] Optionally, the specific surface area of the lithium supplement additive is 1m 2 / g-10m 2 / g. Further, the specific surface area of the lithium supplement additive is 1m 2 / g-5m 2 / g.
[0025] Optionally, the median particle size D50 of the lithium supplement additive is 2 μm-10 μm, D10 / D50≥0.3, and D90 / D50≤2.
[0026] The lithium supplement additive provided in the first aspect of the present application can effectively supplement the loss of lithium ions during the initial charge and discharge process of a lithium secondary battery, thereby improving the initial charge and discharge efficiency of the lithium ion battery and increasing the battery energy density. The lithium supplement additive also has good stability, can exist stably in the air, and has a low amount of residual alkali on the surface, which is conducive to adding it to a lithium secondary battery to achieve lithium supplementation.
[0027] The second aspect of the present application provides a method for preparing a lithium supplement additive, comprising the following steps:
[0028] After the nickel source and the lithium source are fully mixed, the lithium-rich material core precursor is obtained by heat treatment at 500°C-850°C for 10h-48h, and the lithium-rich material core precursor is mixed with a doping source and heat treated at 400°C-700°C for 1h-6h to obtain a lithium-rich material core; the doping source includes a doping element M; the doping element M includes one or more of Cu, Co, Al, Ti, V, Zr and Fe; the lithium-rich material core includes an average chemical formula of aNi x M y O z bLi2O lithium-rich material, wherein 0.95≤x≤1, 0.01≤y≤0.05, 1≤z≤1.15, 0.8≤a≤1.1, 0.8≤b≤1.1; the M comprises one or more of Cu, Co, Al, Ti, V, Zr and Fe;
[0029] The lithium-rich material core is coated with a polymer to form a polymer layer to obtain the lithium supplement additive.
[0030] Optionally, the polymer includes [C6H7O6Na] n Organic polymers with the structure [C6H7O2(OH)2OCH2COONa] n Organic polymers with [C3H4O2] n Organic polymers with the structure [C3H3O2M a ] n Organic polymers with [C3H3N] n An organic polymer with the structure -[CH2-CF2] n -structure, an organic polymer containing -[NHCO]-structure, an organic polymer containing an imide ring -[CO-N-CO]-structure on the main chain, and one or more of polyvinyl pyrrolidone, wherein M a It is an alkali metal element.
[0031] Optionally, after the lithium-rich material core is polymer-coated to form a polymer layer, an electrochemically active layer is prepared on the polymer layer; the electrochemically active layer includes an electrochemically active material.
[0032] Optionally, the electrochemically active material includes one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium fluorovanadium phosphate, lithium titanate and lithium nickel cobalt manganese oxide.
[0033] Optionally, the lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate and lithium oxide.
[0034] Optionally, the nickel source includes one or more of nickel hydroxide, nickel nitrate, nickel chloride, nickel acetate and nickel oxide.
[0035] Optionally, the heat treatment equipment includes any one of a roller kiln, a push plate kiln, a rotary kiln, a rotary kiln or a fluidized bed.
[0036] Optionally, the polymer coating method comprises: mixing the lithium-rich material core with a polymer solution and drying to obtain a polymer layer.
[0037] Optionally, the preparation method of the electrochemically active layer is: mixing a lithium-rich material core having a polymer layer with an electrochemically active material, and allowing the electrochemically active material to accumulate on the surface of the polymer layer to obtain a lithium supplement additive.
[0038] The preparation method of the lithium supplement additive provided in the second aspect of the present application is simple in process and is conducive to industrial production; the prepared lithium supplement additive has low impurity content and good stability, and its application in lithium secondary batteries can greatly improve the cycle stability of the battery.
[0039] The third aspect of the present application provides a secondary battery, comprising a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises the lithium supplement additive provided in the first aspect of the present application.
[0040] The secondary battery provided in the third aspect of the present application has high energy density, cycle performance and safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 A schematic diagram of the structure of a lithium supplement additive provided in one embodiment of the present application;
[0042] Figure 2 A schematic diagram of the structure of a lithium supplement additive provided in one embodiment of the present application;
[0043] Figure 3 A schematic diagram of the structure of a lithium supplement additive provided in one embodiment of the present application;
[0044] Figure 4 This is a scanning electron microscope image of the lithium supplement additive provided in Example 1 of the present application;
[0045] Figure 5 This is a scanning electron microscope image of the lithium supplement additive provided in Example 2 of the present application;
[0046] Figure 6 The X-ray diffraction pattern of the lithium-rich material core provided in Example 2 of the present application;
[0047] Figure 7 This is the X-ray diffraction pattern of the lithium supplement additive provided in Example 2 of the present application. DETAILED DESCRIPTION
[0048] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0049] The present application embodiment provides a lithium supplement additive for supplementing lithium to the positive electrode of a lithium secondary battery. Figure 1 , Figure 1 The schematic diagram of the structure of the lithium supplement additive provided in one embodiment of the present application, the lithium supplement additive comprises a lithium-rich material core 10 and a shell 20 disposed on the lithium-rich material core 10; the lithium-rich material core 10 comprises an average chemical formula of aNi x M y O z bLi2O lithium-rich material, wherein 0.95≤x≤1, 0.01≤y≤0.05, 1≤z≤1.15, 0.8≤a≤1.1, 0.8≤b≤1.1, and M includes one or more of Cu, Co, Al, Ti, V, Zr, and Fe; the shell layer 20 includes a polymer layer 201 coated on the surface of the lithium-rich material core 10.
[0050] In the present application, the lithium-rich material core includes an average chemical formula of aNi x M y O zbLi2O lithium-rich material, wherein 0.95≤x≤1, 0.01≤y≤0.05, 1≤z≤1.15, 0.8≤a≤1.1, 0.8≤b≤1.1, a and b are molar numbers, and M includes one or more of Cu, Co, Al, Ti, V, Zr and Fe. The lithium element in the core of the lithium-rich material can effectively make up for the lithium loss during the first charging of the lithium secondary battery, and the nickel element can strengthen the structural skeleton of the core of the lithium-rich material and improve the structural stability of the core. However, nickel has a certain activity and is prone to side reactions with the electrolyte, reducing the performance of the battery; and the addition of nickel will cause the lithium-supplementing additive to react easily with water or CO2 to generate residual alkali such as lithium carbonate or lithium hydroxide. These residual alkalis will first cause the electrode slurry to easily form a jelly-like shape during the preparation process, which is not conducive to the coating of the electrode slurry; secondly, the residual alkali will cause the positive electrode plate to react with the electrolyte, causing the electrolyte to decompose and produce gas; and these residual alkalis can react with the battery collector at high temperature to release hydrogen, causing the battery to produce gas and expand, and the battery collector is damaged, reducing the safety of the battery. In order to improve the stability of the lithium-supplementing additive and inhibit the generation of residual alkali by the lithium-supplementing additive, the present application doped the metal element M in the lithium-rich material core, and the element M includes one or more of Cu, Co, Al, Ti, V, Zr and Fe. By doping the lithium-rich material core, the crystal structure strength of the lithium-rich material can be enhanced, the reaction activity of lithium and nickel elements to water or CO2 can be reduced, thereby reducing the content of residual alkali and improving the safety and cycle performance of the battery. In some embodiments of the present application, the element M is one or more of Cu and Al. Cu or Al can effectively reduce the activity of nickel element and inhibit the precipitation of residual alkali, which is beneficial to improving the structural stability of lithium supplement additives.
[0051] In some embodiments of the present application, the element M is only doped in the surface layer of the lithium-rich material core, that is, the element M is locally doped in the lithium-rich material core, the part doped with the element M is the doped interface layer, and the part not doped with the element M is the inner layer. This doping method is interface layer doping. Figure 2 , Figure 2The schematic diagram of the structure of the lithium supplement additive provided in one embodiment of the present application, the lithium supplement additive includes a lithium-rich material core 10 and a shell 20 arranged on the surface of the lithium-rich material core 10, wherein the lithium-rich material core 10 includes an inner layer 101 and a doped interface layer 102. In the embodiment of the present application, the content of the element M can be gradually reduced along the direction from the surface of the lithium-rich material core to the center of the lithium-rich material core by doping the interface layer, and the content of the element Li and the element Ni can be gradually increased along the direction from the surface of the lithium-rich material core to the center of the lithium-rich material core. The lithium-rich material core with the above-mentioned element distribution can reduce the influence of the doping element M on the capacity of the lithium supplement additive, ensure the purity of the inner layer of the lithium-rich material core is higher, make the lithium supplement additive have a higher effective capacity, and can reduce the reactivity of the lithium-rich material core, and improve the stability of the lithium supplement additive. In the embodiment of the present application, the thickness of the doped interface layer is 1nm-100nm. The thickness of the doped interface layer can be specifically but not limited to 1nm, 5nm, 10nm, 20nm, 30nm, 50nm, 70nm, 80nm, 90nm or 100nm.
[0052] In the embodiment of the present application, the median particle size D50 of the lithium-rich material core is 2μm-10μm, and the median particle size D50 of the lithium-rich material core can be, but is not limited to, 2μm, 4μm, 5μm, 7μm, 9μm or 10μm. Controlling the median particle size of the lithium-rich material core within the above range is conducive to the lithium supplement additive to achieve rapid and effective lithium supplementation of lithium secondary batteries. In the embodiment of the present application, the particle size D10 / D50 of the lithium-rich material core is ≥0.3, and D90 / D50 is ≤2. Controlling the particle size of the lithium-rich material core in a narrower distribution state can achieve stable electrochemical performance of the lithium supplement additive. In the embodiment of the present application, the mass percentage of the lithium-rich material core in the lithium supplement additive is 90%-99%. In some embodiments of the present application, the mass percentage of the lithium-rich material core in the lithium supplement additive is 95%-99%. The higher the content of the lithium-rich material core, the better the lithium supplement effect of the lithium supplement additive. The mass percentage of the lithium-rich material core to the lithium-supplementing additive may be, but is not limited to, 90%, 92%, 93%, 95%, 98% or 99%.
[0053] In the present application, by providing a shell layer on the surface of the lithium-rich material core, the lithium-rich material core can be prevented from directly contacting with air, reducing the capacity loss caused by the reaction of the lithium-rich material core with water or CO2, reducing the residual alkali amount of the lithium supplement additive, facilitating the preparation of the positive electrode slurry, and achieving effective lithium supplementation for lithium secondary batteries. In the embodiment of the present application, the shell layer includes a polymer layer, and the polymer layer includes a polymer. In the embodiment of the present application, the polymer includes [C6H7O6Na] n Organic polymers with the structure [C6H7O2(OH)2OCH2COONa] nOrganic polymers with [C3H4O2] n Organic polymers with the structure [C3H3O2M a ] n Organic polymers with [C3H3N] n An organic polymer with the structure -[CH2-CF2] n -structure, an organic polymer containing -[NHCO]-structure, an organic polymer containing an imide ring -[CO-N-CO]-structure on the main chain, and one or more of polyvinyl pyrrolidone, wherein M a It is an alkali metal element.
[0054] In some embodiments of the present application, the polymer includes one or more of polyvinylidene fluoride, sodium alginate, sodium carboxymethyl cellulose, polyacrylic acid, polyacrylic acid salt, polyacrylonitrile, polyamide, polyimide and polyvinyl pyrrolidone. In some embodiments of the present application, the polymer includes one or more of sodium carboxymethyl cellulose and polyacrylic acid. Sodium carboxymethyl cellulose and polyacrylic acid are two-dimensional surface polymers with good adhesion, which can effectively coat the lithium-rich material core, thereby avoiding the contact between the lithium-rich material core and the air and improving the stability of the lithium supplement additive. In the embodiment of the present application, the molecular weight of the polymer is greater than or equal to 100,000. The molecular weight of the polymer can be, but is not limited to, 100,000, 150,000, 200,000, 300,000, 500,000 or 1 million. The larger the molecular weight of the polymer, the higher the density and structural strength of the polymer layer, and the more conducive to the protection of the lithium-rich material core.
[0055] In some embodiments of the present application, the polymer layer also includes a conductive agent, and the conductive agent includes one or more of carbon black, graphite, conductive carbon microspheres, carbon nanofibers, carbon nanotubes, C60 and graphene. Adding a conductive agent to the polymer layer can enhance the conductivity of the polymer layer, improve the conductivity of the lithium supplement additive, and facilitate the transmission of electrons and ions. In an embodiment of the present application, the mass ratio of the polymer to the conductive agent is 1: (0.3-1.5), and further, the mass ratio of the polymer to the conductive agent is 1: (0.5-1.2). The mass ratio of the polymer to the conductive agent can be, but is not limited to, 1: 0.3, 1: 0.5, 1: 0.7, 1: 1, 1: 1.2 or 1: 1.5. When the mass ratio of the polymer to the conductive agent is within the above range, the polymer layer can completely cover the lithium-rich material core, improve the stability of the lithium supplement additive, and the polymer layer has good conductivity, which can reduce the electrochemical impedance, thereby effectively increasing the capacity of the battery.
[0056] In an embodiment of the present application, the thickness of the polymer layer is 2nm-50nm, and further, the thickness of the polymer layer is 5nm-40nm. The thickness of the polymer layer can be, but is not limited to, 2nm, 3nm, 5nm, 8nm, 10nm, 15nm, 20nm, 40nm or 50nm. When the polymer layer is within the above thickness range, it can effectively protect the lithium-rich material core without affecting the kinetic transport of ions and electrons, thereby achieving effective lithium replenishment of the battery. In an embodiment of the present application, the mass of the polymer layer accounts for 1%-10% of the total mass of the lithium replenishing additive. The mass percentage of the polymer layer in the lithium replenishing additive can be, but is not limited to, 1%, 2%, 3%, 5%, 7%, 9% or 10%.
[0057] In some embodiments of the present application, the shell layer further comprises an electrochemically active layer disposed on the surface of the polymer layer, and the electrochemically active layer comprises an electrochemically active material. Figure 3 , Figure 3 This is a schematic diagram of the structure of a lithium supplement additive provided in one embodiment of the present application, wherein the lithium supplement additive comprises a lithium-rich material core 10 and a shell 20, wherein the lithium-rich material core 10 comprises an inner layer 101 and a doped interface layer 102; and the shell 20 comprises a polymer layer 201 and an electrochemically active layer 202. In the present application, the electrochemically active layer is provided on the surface of the polymer layer to improve the conductivity of the lithium supplement additive, promote the transport of electrons and ions in the lithium supplement additive, and reduce the electrochemical impedance; and the electrochemically active layer is provided to protect the lithium-rich material core, prevent the lithium-rich material core from contacting with the air, and ensure that the lithium supplement additive has a higher effective capacity.
[0058] In the present application, the electrochemically active layer is formed by the electrochemically active material being attached to the surface of the polymer layer through the bonding effect of the polymer layer and deposited. In the embodiment of the present application, the electrochemically active material includes one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, fluorolithium vanadium phosphate, lithium titanate and lithium nickel cobalt manganate. In some embodiments of the present application, the electrochemically active material also includes carbon, and the mass percentage of carbon in the electrochemically active material is 0.5%-3%. Adding carbon to the electrochemically active material can improve the conductivity of the electrochemically active layer and reduce the electrochemical impedance. In the embodiment of the present application, the particle size of the electrochemically active material is 30nm-200nm. The particle size of the electrochemically active material can be specifically but not limited to 30nm, 40nm, 50nm, 70nm, 100nm, 120nm, 150nm, 170nm or 200nm. The particle size of the electrochemically active material will affect the thickness of the electrochemically active layer. The use of electrochemically active materials with the above-mentioned particle size can not only form an electrochemically active layer with a compact structure, but also the thickness of the electrochemically active layer is moderate, which can achieve a good coating effect. In the embodiment of the present application, the thickness of the electrochemically active layer is 100nm-500nm. The thickness of the electrochemically active layer can be, but not limited to, 100nm, 200nm, 300nm, 400nm or 500nm. In the embodiment of the present application, the mass of the electrochemically active layer accounts for 1%-9% of the total mass of the lithium supplement additive. The mass percentage of the electrochemically active layer in the lithium supplement additive can be, but not limited to, 1%, 2%, 5%, 7% or 9%.
[0059] In the embodiment of the present application, the BET specific surface area of the lithium supplement additive is 1 m 2 / g-10m 2 / g. Furthermore, the BET specific surface area of the lithium supplement additive is 1m 2 / g-5m 2 / g. Controlling the specific surface area of the lithium supplement additive within the above range can ensure the rapid transmission of ions and electrons in the lithium supplement additive, and the area of the lithium supplement additive in contact with the air is smaller, and the risk of reaction is lower, which can ensure that the lithium supplement additive has a higher effective capacity. In the embodiment of the present application, the median particle size D50 of the lithium supplement additive is 2μm-10μm, and the median particle size D50 of the lithium supplement additive can be but is not limited to 2μm, 4μm, 5μm, 7μm, 9μm or 10μm. In the embodiment of the present application, the particle size D10 / D50 of the lithium supplement additive is ≥0.3, and D90 / D50≤2.
[0060] The present application also provides a method for preparing a lithium supplement additive, comprising the following steps:
[0061] Step 100: After the nickel source and the lithium source are fully mixed, heat treatment is performed at 500° C.-850° C. for 10 h-48 h to obtain a lithium-rich material core precursor, and after the lithium-rich material core precursor is mixed with a doping source, heat treatment is performed at 400° C.-700° C. for 1 h-6 h to perform interface layer doping to obtain a lithium-rich material core;
[0062] Step 200: The lithium-rich material core is coated with a polymer to form a polymer layer to obtain a lithium supplement additive.
[0063] In the embodiment of the present application, in step 100, the heat treatment process is carried out in a non-oxidizing atmosphere. In the embodiment of the present application, the non-oxidizing atmosphere includes one or more of nitrogen, helium, argon and hydrogen. In the embodiment of the present application, the heat treatment temperature for preparing the lithium-rich core precursor after mixing the nickel source and the lithium source is 500°C-850°C, and the heat treatment time is 10h-48h. In some embodiments of the present application, the heat treatment temperature for preparing the lithium-rich core precursor is 600°C-700°C, and the heat treatment time is 15h-24h. The heat treatment temperature for preparing the lithium-rich core precursor can be, but not limited to, 500°C, 550°C, 600°C, 650°C, 700°C or 850°C, and the heat treatment time can be, but not limited to, 10h, 15h, 20h, 25h, 30h, 35h, 40h or 48h. In the embodiment of the present application, after the heat treatment is completed, the product is mechanically crushed and classified to obtain a lithium-rich material core precursor.
[0064] In the embodiment of the present application, after obtaining the lithium-rich material core precursor, the lithium-rich material core precursor is mixed with a doping source to perform interface layer doping. In the embodiment of the present application, the temperature of the interface layer doping is 400°C-700°C, and the time of the interface layer doping is 1h-6h. The temperature of the interface layer doping can be, but not limited to, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C, and the time of the interface layer doping can be, but not limited to, 1h, 2h, 4h, 5h or 6h. In the present application, by adopting a step-by-step sintering method, the element M can be made to penetrate inward from the surface layer of the lithium-rich material core, and finally form a structure in which the content of the element M gradually decreases from the surface layer of the lithium-rich material core to the center of the lithium-rich material core, and the content of the element Li and the element Ni gradually increases from the surface layer of the lithium-rich material core to the center of the lithium-rich material core, thereby improving the stability of the lithium-rich material core. In the embodiment of the present application, the heat treatment equipment can be any one of a rotary furnace, a rotary kiln, a box furnace, a tubular furnace, a roller kiln, a push plate kiln or a fluidized bed.
[0065] In an embodiment of the present application, the lithium source includes one or more of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate and lithium oxide. The nickel source includes one or more of nickel hydroxide, nickel nitrate, nickel chloride, nickel acetate and nickel oxide. In an embodiment of the present application, the doping source includes a metal element M, and the doping source may be one or more of an oxide, hydroxide or salt of the metal element M. In an embodiment of the present application, the metal element M includes one or more of Cu, Co, Al, Ti, V, Zr and Fe;
[0066] In an embodiment of the present application, in step 200, the preparation method of the polymer layer is specifically as follows: a lithium-rich material core is mixed with a polymer solution, and the polymer layer is obtained after drying. The polymer layer can be completely coated on the surface of the lithium-rich material core by solution mixing, thereby improving the stability of the lithium supplement additive. In an embodiment of the present application, the lithium-rich material core and the polymer solution are mixed for 1h-5h. In an embodiment of the present application, the polymer solution includes a solvent and a polymer. In an embodiment of the present application, the solvent of the polymer solution includes one or more of N-methylpyrrolidone, methanol, ethanol, isopropanol, acetone, tetrahydrofuran and diethyl ether. In some embodiments of the present application, the polymer includes [C6H7O6Na] n Organic polymers with the structure [C6H7O2(OH)2OCH2COONa] n Organic polymers with [C3H4O2] n Organic polymers with the structure [C3H3O2M a ] n Organic polymers with [C3H3N] n An organic polymer with the structure -[CH2-CF2] n -structure, an organic polymer containing -[NHCO]-structure, an organic polymer containing an imide ring -[CO-N-CO]-structure on the main chain, and one or more of polyvinyl pyrrolidone, wherein M a It is an alkali metal element.
[0067] In some embodiments of the present application, the polymer solution includes a solvent, a conductive agent and a polymer. When the polymer solution contains a conductive agent, the polymer can play a bonding role and can be coated together with the conductive agent on the surface of the lithium-rich material core to form a polymer layer. In some embodiments of the present application, the conductive agent includes one or more of carbon black, graphite, conductive carbon microspheres, carbon nanofibers, carbon nanotubes, C60 and graphene. In some embodiments of the present application, the mass ratio of the polymer to the conductive agent in the polymer solution is 1: (0.3-1.5). The mass ratio of the polymer to the conductive agent can be specifically but not limited to 1: 0.3, 1: 0.5, 1: 0.7, 1: 1 or 1: 1.5.
[0068] In the embodiments of the present application, the solid content of the polymer solution is 0.3wt%-5wt%, and the solid content of the polymer solution can be, but is not limited to, 0.3wt%, 0.5wt%, 0.7wt%, 1wt%, 2wt%, 4wt% or 5wt%. In some embodiments of the present application, the method of drying after mixing the lithium-rich material core with the polymer solution is spray drying.
[0069] In some embodiments of the present application, after the polymer layer is formed, an electrochemically active layer may be prepared on the polymer layer. In the embodiments of the present application, the method for preparing the electrochemically active layer is as follows: a lithium-rich material core having a polymer layer is mixed with an electrochemically active material, and the electrochemically active material is deposited on the surface of the polymer layer to form an electrochemically active layer, thereby obtaining a lithium supplement additive.
[0070] In the embodiment of the present application, the lithium-rich material core is mixed with the electrochemically active material in a manner including mechanical stirring and mechanical fusion. During the mixing process, not only is the polymer layer sticky enough to bond the electrochemically active material, but also because the electrochemically active material is subjected to a large physical extrusion force, it is tightly stacked on the surface of the polymer layer to form an electrochemically active layer. In the embodiment of the present application, the mixing speed is greater than or equal to 3000rpm, and a higher speed is conducive to forming a tightly structured electrochemically active layer. The mixing speed may be, but is not limited to, 3000rpm, 4000rpm, 5000rpm, 6000rpm, 7000rpm or 8000rpm. In the embodiment of the present application, the mixing time is 5min-30min. The mixing time may be, but is not limited to, 5min, 10min, 15min, 20min, 25min or 30min.
[0071] The present application reduces the reactivity of lithium and nickel in the lithium-rich material core by doping the lithium-rich material core with an interface layer; and also coats the lithium-rich material core, and the polymer layer can effectively isolate the lithium-rich material core from the air, thereby inhibiting the reaction of lithium and nickel with the air, inhibiting the generation of residual alkali, and ensuring the storage stability and processing stability of the lithium-supplementing additive, which is beneficial to the production, storage and use of the lithium-supplementing additive; the coating layer also has a high conductivity, which is beneficial to the capacity of the lithium-rich material core, thereby achieving efficient lithium supplementation. The preparation method is simple in process, convenient in operation, and the obtained lithium-supplementing additive has good stability and is suitable for large-scale production.
[0072] The present application also provides a lithium secondary battery, comprising a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate comprises the lithium supplement additive provided in the present application. The positive electrode plate comprises a current collector and a positive electrode material layer arranged on the current collector. The current collector comprises any one of copper foil and aluminum foil; the positive electrode material layer comprises an electrode active material, a lithium supplement additive, a binder and a conductive agent, wherein the lithium supplement additive comprises the lithium supplement additive provided in the first aspect of the present application. In an embodiment of the present application, the binder comprises one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives. In an embodiment of the present application, the conductive agent comprises one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes. In the embodiment of the present application, the electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium fluorinated vanadium phosphate, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide. In the embodiment of the present application, the preparation process of the positive electrode plate is: the electrode active material, lithium supplement additive, conductive agent and binder are mixed to obtain electrode slurry, the electrode slurry is coated on the current collector, and the positive electrode plate is prepared through drying, rolling, die cutting and other steps.
[0073] The lithium secondary battery provided by the present application has good cycle performance and safety performance due to the use of the lithium supplement additive of the present application, which is conducive to the application of lithium secondary batteries in various fields.
[0074] The following is a further description of the implementation of the present application with reference to a number of embodiments.
[0075] Example 1
[0076] 1) Preparation of lithium-rich material core
[0077] NiO and Li2O were mixed uniformly in a molar ratio of 1:1, and heated to 680°C at a rate of 5°C / min under nitrogen protection and kept warm for 20 hours. After cooling, the product was mechanically crushed and classified to obtain NiO·Li2O powder (lithium-rich material core precursor). NiO·Li2O powder was mixed uniformly with aluminum nitrate in a molar ratio of 98:2, and kept warm at 600°C for 6 hours to obtain the lithium-rich material core. The chemical formula of the lithium-rich material core is Ni 0.98 Al 0.02 O 1.01 0.98Li2O.
[0078] 2) Preparation of lithium supplement additives
[0079] 500 g of coating solution A was prepared, the solvent was N-methylpyrrolidone, the solution contained 0.3 wt % of polyvinylpyrrolidone and 0.3 wt % of carbon nanotubes, 100 g of lithium-rich material core was added to the coating solution and stirred for 2 h, and then spray-dried to form a polymer layer to obtain a lithium supplement additive.
[0080] 3) Preparation of lithium secondary batteries
[0081] The lithium supplement additive is combined with NCM523 (positive electrode active material, LiNi 0.5 Co 0.2 Mn 0.3 O2) mixing the mixture in a mass ratio of 5:95 to obtain a mixture, mixing the mixture with polyvinylidene fluoride and carbon nanotubes in a mass ratio of 93:3:4, adding polyvinyl pyrrolidone and stirring by ball milling to obtain a positive electrode slurry, coating the positive electrode slurry on the surface of aluminum foil, rolling, and vacuum drying at 110° C. overnight to obtain a positive electrode sheet;
[0082] Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF6 was added to form an electrolyte, and the concentration of LiPF6 was 1 mol / L. A positive electrode sheet, a polypropylene microporous separator, a lithium sheet and an electrolyte were assembled to obtain a lithium secondary battery.
[0083] Example 2
[0084] 1) Preparation of lithium-rich material core
[0085] Same as Example 1
[0086] 2) Preparation of lithium supplement additives
[0087] Prepare 500g of coating solution A, the solvent is N-methylpyrrolidone, the solution contains 0.3wt% of polyvinylpyrrolidone and 0.3wt% of carbon nanotubes, add 100g of lithium-rich material core into the coating solution and stir for 2h, then form a polymer layer by spray drying, add the lithium-rich material core with the polymer layer and lithium iron phosphate with a size of 80nm into a mechanical fusion machine, wherein the mass ratio of the lithium-rich material core with the polymer layer to the lithium iron phosphate is 1:0.05, and fuse the two at a speed of 5000rpm for 15min to obtain a lithium supplement additive.
[0088] 3) Preparation of lithium secondary batteries
[0089] Same as Example 1.
[0090] Example 3
[0091] 1) Preparation of lithium-rich material core
[0092] NiO and Li2O were mixed uniformly in a molar ratio of 1:1, and heated to 680°C at a rate of 5°C / min under nitrogen protection and kept warm for 20 hours. After cooling, the product was mechanically crushed and classified to obtain NiO·Li2O powder (lithium-rich material core precursor). NiO·Li2O powder and copper nitrate were mixed uniformly in a molar ratio of 95:5, and kept warm at 600°C for 6 hours to obtain the lithium-rich material core. The chemical formula of the lithium-rich material core is Ni 0.95 Cu 0.05 O·0.95Li2O.
[0093] 2) Preparation of lithium supplement additives
[0094] Prepare 500g of coating solution A, the solvent is tetrahydrofuran, the solution contains 0.15wt% polyacrylic acid and 0.3wt% graphene, add 100g lithium-rich material core into the coating solution and stir for 2h, then form a polymer layer by spray drying, add the lithium-rich material core with the polymer layer and lithium iron manganese phosphate with a size of 50nm into a mechanical fusion machine, wherein the mass ratio of the lithium-rich material core with the polymer layer to the lithium iron manganese phosphate is 1:0.05, and fuse the two at a speed of 3000rpm for 30min to obtain a lithium supplement additive.
[0095] 3) Preparation of lithium secondary batteries
[0096] Same as Example 1
[0097] Example 4
[0098] 1) Preparation of lithium-rich material core
[0099] NiO and Li2O were mixed uniformly in a molar ratio of 1:1, and heated to 650°C at a rate of 5°C / min under nitrogen protection and kept warm for 17 hours. After cooling, the product was mechanically crushed and classified to obtain NiO·Li2O powder (lithium-rich material core precursor). NiO·Li2O powder was mixed uniformly with titanium dioxide in a molar ratio of 95:5, and kept warm at 600°C for 6 hours to obtain the lithium-rich material core. The chemical formula of the lithium-rich material core is Ni 0.95 Ti 0.05 O·0.95Li2O.
[0100] 2) Preparation of lithium supplement additives
[0101] Prepare 500g of coating solution A, the solvent is tetrahydrofuran, the solution contains 0.3wt% sodium carboxymethyl cellulose and 0.3wt% conductive carbon black, add 100g lithium-rich material core into the coating solution and stir for 3h, then spray dry to form a polymer layer, add the lithium-rich material core with the polymer layer and lithium iron manganese phosphate with a size of 80nm into a mechanical fusion machine, wherein the mass ratio of the lithium-rich material core with the polymer layer to the lithium iron manganese phosphate is 1:0.05, and fuse the two at a speed of 3000rpm for 30min to obtain a lithium supplement additive.
[0102] 3) Preparation of lithium secondary batteries
[0103] Same as Example 1
[0104] Example 5
[0105] 1) Preparation of lithium-rich material core
[0106] NiO and Li2O were mixed uniformly at a molar ratio of 1:0.95, and the temperature was raised to 680°C at a rate of 5°C / min under nitrogen protection and kept warm for 20 hours. After cooling, the product was mechanically crushed and classified to obtain NiO·0.95Li2O powder (lithium-rich material core precursor). NiO·0.95Li2O powder was mixed uniformly with copper nitrate at a molar ratio of 98:2, and kept warm at 600°C for 6 hours to obtain the lithium-rich material core. The chemical formula of the lithium-rich material core is Ni 0.98 Cu 0.02 O·0.931Li2O.
[0107] 2) Preparation of lithium supplement additives
[0108] Prepare 500g of coating solution A, the solvent is tetrahydrofuran, the solution contains 0.15wt% polyacrylic acid and 0.3wt% graphene, add 100g lithium-rich material core into the coating solution and stir for 2h, then form a polymer layer by spray drying, add the lithium-rich material core with the polymer layer and lithium iron manganese phosphate with a size of 50nm into a mechanical fusion machine, wherein the mass ratio of the lithium-rich material core with the polymer layer to the lithium iron manganese phosphate is 1:0.05, and fuse the two at a speed of 3000rpm for 30min to obtain a lithium supplement additive.
[0109] 3) Preparation of lithium secondary batteries
[0110] Same as Example 1
[0111] Example 6
[0112] 1) Preparation of lithium-rich material core
[0113] NiO and Li2O were mixed uniformly at a molar ratio of 1:0.95, and the temperature was raised to 680°C at a rate of 5°C / min under nitrogen protection and kept warm for 20 hours. After cooling, the product was mechanically crushed and classified to obtain NiO·0.95Li2O powder (lithium-rich material core precursor). NiO·0.95Li2O powder was mixed uniformly with aluminum nitrate at a molar ratio of 96:4, and kept warm at 600°C for 6 hours to obtain the lithium-rich material core. The chemical formula of the lithium-rich material core is Ni 0.96 Al 0.04 O 1.02 0.912Li2O.
[0114] 2) Preparation of lithium supplement additives
[0115] Prepare 500g of coating solution A, the solvent is tetrahydrofuran, the solution contains 0.15wt% polyacrylic acid and 0.3wt% graphene, add 100g lithium-rich material core into the coating solution and stir for 2h, then form a polymer layer by spray drying, add the lithium-rich material core with the polymer layer and lithium iron manganese phosphate with a size of 50nm into a mechanical fusion machine, wherein the mass ratio of the lithium-rich material core with the polymer layer to the lithium iron manganese phosphate is 1:0.05, and fuse the two at a speed of 3000rpm for 30min to obtain a lithium supplement additive.
[0116] 3) Preparation of lithium secondary batteries
[0117] Same as Example 1
[0118] Example 7
[0119] 1) Preparation of lithium-rich material core
[0120] NiO and Li2O were mixed uniformly at a molar ratio of 1:0.9, and the temperature was raised to 680°C at a rate of 5°C / min under nitrogen protection and kept warm for 20 hours. After cooling, the product was mechanically crushed and classified to obtain NiO·0.9Li2O powder (lithium-rich material core precursor). NiO·0.9Li2O powder and cobalt nitrate were mixed uniformly at a molar ratio of 95:5, and kept warm at 600°C for 6 hours to obtain the lithium-rich material core. The chemical formula of the lithium-rich material core is Ni 0.95 Co 0.05 O·0.855Li2O.
[0121] 2) Preparation of lithium supplement additives
[0122] Prepare 500g of coating solution A, the solvent is tetrahydrofuran, the solution contains 0.15wt% polyacrylic acid and 0.3wt% graphene, add 100g lithium-rich material core into the coating solution and stir for 2h, then form a polymer layer by spray drying, add the lithium-rich material core with the polymer layer and lithium iron manganese phosphate with a size of 50nm into a mechanical fusion machine, wherein the mass ratio of the lithium-rich material core with the polymer layer to the lithium iron manganese phosphate is 1:0.05, and fuse the two at a speed of 3000rpm for 30min to obtain a lithium supplement additive.
[0123] 3) Preparation of lithium secondary batteries
[0124] Same as Example 1
[0125] In order to demonstrate the beneficial effects of the embodiments of the present application, a comparative example is set up.
[0126] Comparative Example 1
[0127] 1) Preparation of lithium supplement additives
[0128] NiO and Li2O were uniformly mixed in a molar ratio of 1:1, and under nitrogen protection, the temperature was raised to 680°C at a rate of 5°C / min and kept warm for 20 hours. After cooling, the product was mechanically crushed and classified to obtain NiO·Li2O powder (lithium supplement additive).
[0129] 2) Preparation of lithium secondary batteries
[0130] Same as Example 1
[0131] Comparative Example 2
[0132] 1) Preparation of lithium supplement additives
[0133] NiO and Li2O are uniformly mixed in a molar ratio of 1:1, and the temperature is raised to 680°C at a rate of 5°C / min under nitrogen protection and kept warm for 20 hours. After cooling, the product is mechanically crushed and classified to obtain NiO·Li2O powder; 500g of coating solution A is prepared, the solvent is N-methylpyrrolidone, and the solution contains 0.3wt% of polyvinylpyrrolidone and 0.3wt% of carbon nanotubes. 100g of NiO·Li2O powder is added to the coating solution and stirred for 2 hours, and then spray-dried to form a polymer layer to obtain a lithium supplement additive.
[0134] 2) Preparation of lithium secondary batteries
[0135] Same as Example 1
[0136] Comparative Example 3
[0137] 1) Preparation of lithium supplement additives
[0138] NiO and Li2O are uniformly mixed in a molar ratio of 1:1, and the temperature is raised to 680°C at a rate of 5°C / min and kept warm for 20 hours under nitrogen protection. After cooling, the product is mechanically crushed and classified to obtain NiO·Li2O powder; 500g of coating solution A is prepared, the solvent is N-methylpyrrolidone, and the solution contains 0.3wt% of polyvinylpyrrolidone and 0.3wt% of carbon nanotubes, 100g of NiO·Li2O powder is added to the coating solution and stirred for 2h, and then spray-dried to form a polymer layer, and a lithium-rich material core with a polymer layer and lithium iron phosphate with a size of 80nm are added into a mechanical fusion machine, wherein the mass ratio of the lithium-rich material core with a polymer layer to the lithium iron phosphate is 1:0.05, and the two are fused at a speed of 5000rpm for 15min to obtain a lithium supplement additive.
[0139] 2) Preparation of lithium secondary batteries
[0140] Same as Example 1.
[0141] Effect Example
[0142] 1) The morphology of the lithium supplement additives of Example 1 and Example 2 was characterized by scanning electron microscopy, see Figure 4 and Figure 5 ,in, Figure 4 This is a scanning electron microscope image of the lithium supplement additive provided in Example 1 of the present application. Figure 5 This is a scanning electron microscope image of the lithium supplement additive provided in Example 2 of the present application. Figure 4 It can be seen that in the lithium supplement additive of Example 1, the polymer layer is tightly wrapped around the surface of the lithium-rich material core to form a relatively smooth protective layer. Figure 5 It can be seen that the surface of the lithium supplement additive in Example 2 has a large amount of granular substances, which are electrochemically active materials. The electrochemically active materials are tightly combined to form an electrochemically active layer, thereby protecting the lithium-rich material core and inhibiting the reaction between the lithium-rich material core and the air.
[0143] 2) X-ray diffraction characterization of the lithium-rich material core and lithium-supplementing additive of Example 2 is performed, see Figure 6 and Figure 7 ,in, Figure 6 The X-ray diffraction pattern of the lithium-rich material core provided in Example 2 of the present application, Figure 7 This is the X-ray diffraction pattern of the lithium supplement additive provided in Example 2 of the present application. Figure 6 It can be seen that the core of the lithium-rich material has a diffraction peak of NiO. Figure 7 It can be seen that the lithium supplement additive has not only the diffraction peak of NiO but also the diffraction peak of lithium iron phosphate, which indicates that the lithium iron phosphate has been successfully coated to form an electrochemically active layer.
[0144] 3) The content of doping element M in the lithium supplement additives of Examples 1-4 was analyzed by inductively coupled plasma (ICP) emission spectrometry. Please refer to Table 1 for the test results. The y value of doping element M in Table 1 is the content of doping element M in the lithium supplement additive.
[0145] 4) The residual alkali content of the lithium supplement additives of Examples 1-4 and Comparative Examples 1-3 was tested. The specific testing method is as follows: 5g of the lithium supplement additives of Examples 1-4 and Comparative Examples 1-3 were weighed respectively, and 50mL of ultrapure water freed from carbon dioxide was added to dissolve in a beaker. The sample was ultrasonically oscillated for 5 minutes at an ultrasonic frequency of 5KHz and a power of 50w, and stirred every 1 minute; the mixed solution was filtered into a 100ml volumetric flask with quantitative paper and the volume was fixed. Take the above sample solution, titrate it with a standard hydrochloric acid solution, and record the volumes V1 and V2 of the consumed standard hydrochloric acid solution, where V1 is the volume of the standard HCl solution consumed by titration to the first hop point; V2 is the volume of the standard HCl solution consumed from the first hop point to the second hop point. Calculate OH according to the following formula - and CO3 2- Residual alkali content:
[0146]
[0147] Wherein, m is the actual mass of the sample, c is the concentration of the HCl standard solution, V3 is the volume of the filtrate, and V4 is the volume of the filtrate after constant volume to 100 ml. Please refer to Table 1 for the residual alkali content of the lithium supplement additives of Examples 1-4 and Comparative Examples 1-3.
[0148] 5) The electrochemical properties of the lithium secondary batteries of Examples 1-4 and Comparative Examples 1-3 were tested. The test conditions were as follows: the assembled batteries were placed at room temperature for 24 hours and then subjected to charge and discharge tests. The charge and discharge voltage was 2.7V-4.3V. For the electrochemical properties of the lithium secondary batteries of Examples 1-4 and Comparative Examples 1-3, please refer to Table 1.
[0149] Table 1 Experimental parameters of lithium supplement additives and lithium ion batteries of Examples 1-4 and Comparative Examples 1-2
[0150]
[0151] It can be seen from Table 1 that the lithium supplement additives of Examples 1-4 of the present application have low residual alkali content, the prepared positive electrode slurry does not show jelly phenomenon, is easy to coat, and when added to a lithium secondary battery, the battery can have a high initial efficiency and good cycle stability, thereby improving the performance of the lithium ion battery.
[0152] It can be seen from the comparative example experiments that the lithium supplement additive of comparative example 1 does not have a polymerized layer, so the residual alkali content is much greater than that of the lithium supplement additives of embodiments 1-7, and in the preparation process of the positive electrode slurry, due to the high residual alkali content, the positive electrode slurry absorbs a large amount of water to form jelly, which is not conducive to the coating of the positive electrode slurry.
[0153] It can be seen from Example 1 and Comparative Example 2 that the residual alkali content of the lithium supplement additive in Example 1 is low after being doped in the interface layer, and the prepared lithium secondary battery has high first efficiency and cycle performance.
[0154] It can be seen from Example 1 and Example 2 that the provision of an electrochemically active layer can further reduce the residual alkali content of the lithium supplement additive, which is beneficial to the application of the lithium supplement additive in lithium secondary batteries.
[0155] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A lithium supplement additive, characterized in that: The lithium supplement additive comprises a lithium-rich material core and a shell layer arranged on the lithium-rich material core, wherein the lithium-rich material core comprises an average chemical formula of aNi x M y O z bLi2O lithium-rich material, wherein 0.95≤x≤1, 0.01≤y≤0.05, 1≤z≤1.15, 0.8≤a≤1.1, 0.8≤b≤1.1, element M includes one or more of Cu, Co, Al, Ti, V, Zr and Fe; the shell layer includes a polymer layer; the shell layer also includes an electrochemically active layer arranged on the surface of the polymer layer, the electrochemically active layer includes an electrochemically active material, the electrochemically active material includes one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, fluorolithium vanadium phosphate, lithium titanate and lithium nickel cobalt manganese oxide; the lithium-rich material core includes An inner layer and a doped interface layer, wherein the doped interface layer is arranged on at least a portion of the surface of the inner layer; the element M is located in the doped interface layer; the element M is only doped in the surface layer of the lithium-rich material core, the element M is locally doped in the lithium-rich material core, the portion doped with the element M is the doped interface layer, and the portion not doped with the element M is the inner layer; the content of the element M in the doped interface layer gradually decreases along the direction from the surface layer of the lithium-rich material core to the center of the lithium-rich material core, and the content of the element Li and the element Ni gradually increases along the direction from the surface layer of the lithium-rich material core to the center of the lithium-rich material core.
2. The lithium supplement additive according to claim 1, characterized in that: The thickness of the doped interface layer is 1nm-100nm.
3. The lithium supplement additive according to claim 1, characterized in that: The median particle size D50 of the lithium-rich material core is 2 μm-10 μm, D10 / D50≥0.3, and D90 / D50≤2.
4. The lithium supplement additive according to claim 1, characterized in that: The polymer layer includes a polymer; the polymer includes [C6H7O6Na] n Organic polymers with the structure [C6H7O2(OH)2OCH2COONa] n Organic polymers with [C3H4O2] n Organic polymers with the structure [C3H3O2M a ] n Organic polymers with the structure [C3H3N] n An organic polymer with the structure -[CH2-CF2] n -structure, an organic polymer containing -[NHCO]-structure, an organic polymer containing an imide ring -[CO-N-CO]-structure on the main chain, and one or more of polyvinyl pyrrolidone, wherein M a It is an alkali metal element.
5. The lithium supplement additive according to claim 1, characterized in that: The polymer layer also includes a conductive agent; the conductive agent includes one or more of carbon black, graphite, conductive carbon microspheres, carbon nanofibers, carbon nanotubes, C60 and graphene; in the polymer layer, the mass ratio of the polymer to the conductive agent is 1: (0.3-1.5).
6. The lithium supplement additive according to claim 1, characterized in that: The thickness of the polymer layer is 2nm-50nm.
7. The lithium supplement additive according to claim 1, characterized in that: The thickness of the electrochemical active layer is 100nm-500nm.
8. A method for preparing the lithium supplement additive according to any one of claims 1 to 7, characterized in that: include: After the nickel source and the lithium source are fully mixed, the reaction is carried out at 500°C-850°C for 10h-48h to obtain a lithium-rich material core precursor, and the lithium-rich material core precursor is mixed with a doping source and reacted at 400°C-700°C for 1h-6h to obtain a lithium-rich material core; the doping source includes a doping element M; the doping element M includes one or more of Cu, Co, Al, Ti, V, Zr and Fe; the lithium-rich material core includes an average chemical formula of aNi x M y O z bLi2O lithium-rich material, wherein 0.95≤x≤1, 0.01≤y≤0.05, 1≤z≤1.15, 0.8≤a≤1.1, 0.8≤b≤1.1; the M comprises one or more of Cu, Co, Al, Ti, V, Zr and Fe; The lithium-rich material core is coated with a polymer to form a polymer layer to obtain a lithium supplement additive.
9. The preparation method according to claim 8, characterized in that: Also includes: After forming the polymer layer, an electrochemically active layer is prepared on the polymer layer; the electrochemically active layer includes an electrochemically active material.
10. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The positive electrode plate includes the lithium supplement additive according to any one of claims 1 to 7.
Citation Information
Patent Citations
Lithium-rich manganese-based composite anode material of core-shell structure and preparation method thereof
CN108091843A
Silicon-based negative electrode material and lithium ion battery
CN112310372A